Expert review – identification of intra-partum fetal compromise. (July 2015) - Prior, Tomas; Kumar, Sailesh
Abstract: Whilst most cases of cerebral palsy occur as a consequence of an ante-natal insult, a significant proportion, particularly in the term fetus, are attributable to intra-partum hypoxia. Intra-partum monitoring using continuous fetal heart rate assessment has led to an increased incidence of operative delivery without a concurrent reduction in the incidence of cerebral palsy. Despite this, birth asphyxia remains the strongest and most consistent risk factor for cerebral palsy in term infants. This review evaluates current intra-partum monitoring techniques as well as alternative approaches aimed at better identification of the fetus at risk of compromise in labour.